Case series of gingival granular cell tumor—A revelation in neonates. Issue 4 (July 2016) - Pathak, Manish; Narula, Dipanshu
Abstract: Congenital gingival granular cell tumor or congenital epulis is a rare lesion. It is typically seen as a mass protruding out of the newborn child's mouth, which may interfere with respiration or feeding. The lesion behaves in a benign manner without any evidence of recurrence or metastasis. We present three cases here, wherein the clinical features, differential diagnosis, histogenesis and treatment are discussed.